1996
DOI: 10.1111/j.1530-0277.1996.tb01054.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Ethanol Exposure: Hypothalamic‐Pituitary‐Adrenal and β‐Endorphin Responses to Repeated Stress

Abstract: Previous studies provide evidence that fetal ethanol exposure induces hypothalamic-pituitary-adrenal (HPA) and pituitary beta-endorphin (beta-EP) hyperresponsiveness to acute stressors. The present study demonstrates significant effects of in utero ethanol exposure on the parallel response patterns of the HPA axis and the pituitary beta-EP system to repeated exposures to a stressor, restraint stress, and indicates sex differences in response. Together, data from the two experiments indicate that, after repeate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
74
3
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(89 citation statements)
references
References 41 publications
10
74
3
2
Order By: Relevance
“…It has been shown that the neurotransmitter system that regulates the neuroendocrine response to stress is especially vulnerable to ethanol during the developmental period in rats. Behavioral and neurochemical studies indicate that defects in the ability of these rats to respond appropriately to stress seem to be because of alterations in the function of hypothalamic peptides (Weinberg et al, 1996). ␤-EP is one of these peptides that participates in bringing about the body's homeostasis after a stress response (Plotsky, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the neurotransmitter system that regulates the neuroendocrine response to stress is especially vulnerable to ethanol during the developmental period in rats. Behavioral and neurochemical studies indicate that defects in the ability of these rats to respond appropriately to stress seem to be because of alterations in the function of hypothalamic peptides (Weinberg et al, 1996). ␤-EP is one of these peptides that participates in bringing about the body's homeostasis after a stress response (Plotsky, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…First, FAE offspring are known to be stress-hyper-responsive. 47,48 Hence, a visual platform test at the beginning of the training could affect the results of the spatial learning task differentially. Presenting the visual platform at the end of the training would not differentiate the learning impairment from the visual impairment.…”
Section: Forced Swim Testmentioning
confidence: 99%
“…Animal and human studies have demonstrated that environmental manipulation, such as exposure to alcohol or stress during the pre-and early postnatal period (Liang and Boyce 1993;Weinberg et al 1996;Day et al 1998), can modify an organism's response to stressors. Such manipulations may lead to an increased reactivity to stressors ("sensitization"), which can be expressed both behaviourally and neurochemically (Pitman et al 1990;Badiani et al 1996;Pani et al 2000).…”
Section: Previous Studies Have Demonstrated That Exposure To Psychostmentioning
confidence: 99%
“…A wealth of evidence suggests that an increased reactivity to stressors and/or the inability to respond effectively and appropriately to stressors plays an important role in the development and expression of many forms of mental illness (Ehlert and Straub 1998;Kreek and Koob 1998;Dohrenwend 2000;Heim et al 2000). Clearly, a better understanding of the underlying neurobiology of this sensitivity to stressors may help in the prophylaxis and treatment of these disorders.Animal and human studies have demonstrated that environmental manipulation, such as exposure to alcohol or stress during the pre-and early postnatal period (Liang and Boyce 1993;Weinberg et al 1996;Day et al 1998), can modify an organism's response to stressors. Such manipulations may lead to an increased reactivity to stressors ("sensitization"), which can be expressed both behaviourally and neurochemically (Pitman et al 1990;Badiani et al 1996;Pani et al 2000).…”
mentioning
confidence: 99%